Analyze The Level of Goal Shooting Ability with Hit and Push Techniques in Outdoor Hockey Athletes - Andi Rizal; Muh. Aswar; Ramli Ramli (JUARA : Jurnal Olahraga, 2023)
This type of quantitative descriptive research is definite about the ability of goal shooting with hit and push techniques in outdoor hockey athletes in South Sulawesi, which is suspected to be largely lacking. This study aimed to determine the shooting ability level with the hit and push technique of South Sulawesi outdoor hockey athletes. They use a survey method on a population of all outdoor hockey athletes, with 12 people taken using purposive sampling. Data collection techniques using the goal shooting test include hit and push strategies. The data analysis technique used is descriptive analysis in the form of percentages. The results showed that the goal-shooting ability of South Sulawesi outdoor hockey athletes was in the "Medium" category, with the highest frequency and rate, namely the results showed that the goal shooting ability of South Sulawesi outdoor hockey athletes was in the medium class. With a score between 431.8 to 58.75 points, as many as 7 athletes (58.3%) include the ability to hit with a value of 431.07 - 485.88 in the medium category or 75% and the ability to push with a value of 506.66 - 585 .75 points in the moderate category.